2010
DOI: 10.1097/nen.0b013e3181ebe581
|View full text |Cite
|
Sign up to set email alerts
|

Brain Aquaporin-4 in Experimental Acute Liver Failure

Abstract: Intracranial hypertension due to brain edema and associated astrocyte swelling is a potentially lethal complication of acute liver failure (ALF). Mechanisms of edema formation are not well understood but elevated levels of blood and brain ammonia and its byproduct glutamine have been implicated in this process. We examined mRNA and protein expression of the water channel protein aquaporin-4 (AQP4) in cerebral cortex in a rat model of ALF induced by the hepatotoxin thioacetamide. Rats with ALF showed increased … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
40
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 51 publications
(43 citation statements)
references
References 81 publications
(84 reference statements)
3
40
0
Order By: Relevance
“…A study by Wright et al (Wright et al, 2010), found no change in total tissue levels of AQP4 in brain in a rat model of ALF induced by galactosamine, which is in agreement with observations by other investigators (Eefsen et al, 2010; Rama Rao et al, 2010). Based on this finding, these investigators postulated that AQP4 plays no role in the brain edema in ALF.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…A study by Wright et al (Wright et al, 2010), found no change in total tissue levels of AQP4 in brain in a rat model of ALF induced by galactosamine, which is in agreement with observations by other investigators (Eefsen et al, 2010; Rama Rao et al, 2010). Based on this finding, these investigators postulated that AQP4 plays no role in the brain edema in ALF.…”
Section: Discussionsupporting
confidence: 88%
“…However, this study, did not examine levels of AQP4 in the plasma membrane, the site where AQP4 facilitates water movement. Such plasma membrane increase in AQP4 was found in brains of rats with ALF (Eefsen et al, 2010; Rama Rao et al, 2010). Complementary to our observations, a recent study also reported increased plasma membrane levels of AQP4 in human postmortem cerebral cortex from patients with ALF (Thumburu et al, 2013).…”
Section: Discussionmentioning
confidence: 66%
See 2 more Smart Citations
“…Aquaporin-4 has been implicated in the development of brain edema in ALF (Eefsen et al, 2010; Rama Rao et al, 2010). However, the role of aquaporin channels in ALF is uncertain (Wright et al, 2010).…”
Section: Increased Bbb Permeability Occurs Without Overt Bbb Breakdowmentioning
confidence: 99%